2009
DOI: 10.1016/j.appet.2008.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a scale to measure Latino parenting strategies related to children’s obesigenic behaviors. The parenting strategies for eating and activity scale (PEAS)

Abstract: Research has shown that children's dietary and activity-related behaviors are shaped by the family environment and parenting behaviors. The present study describes the development and validation of a bilingual (Spanish and English) scale assessing parenting strategies associated with children's dietary and activity-related behaviors in the home. Items were generated from focus groups with Latina mothers and a review of the literature, and two different samples were used to assess the scale's psychometric prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
122
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(130 citation statements)
references
References 35 publications
4
122
0
4
Order By: Relevance
“…The PEAS was tested in a sample of Latino women to evaluate a wider range of parenting strategies and demonstrated moderate to high internal consistency (a 5 0?81-0?82) (60) . Construct validity was established for the PEAS by correlating the subscales with the appropriate subscales of a child feeding questionnaire.…”
Section: Media Equipment Availabilitymentioning
confidence: 99%
“…The PEAS was tested in a sample of Latino women to evaluate a wider range of parenting strategies and demonstrated moderate to high internal consistency (a 5 0?81-0?82) (60) . Construct validity was established for the PEAS by correlating the subscales with the appropriate subscales of a child feeding questionnaire.…”
Section: Media Equipment Availabilitymentioning
confidence: 99%
“…Four items were averaged to create a measure of limit setting of sedentary behaviors. Construct validity of the PEAS was supported through comparison of the scale with the Child Feeding Questionnaire (Birch et al, 2001) among a sample of ethnically diverse parents (Larios et al, 2009); study results demonstrated positive correlations between the PEAS subscales and subscales on the Child Feeding Questionnaire. In addition, positive correlations shown between the PEAS and parental use of strategies for reducing child fat intake support concurrent validity of the tool as findings suggest that parents who use behavioral strategies for fat and fiber were also more likely to use parenting strategies that promote a healthy lifestyle.…”
Section: Parental Limit Setting Of Sedentary Behaviorsmentioning
confidence: 99%
“…The limiting-activity subscale of the parenting strategies for eating and activity scale (PEAS; Arredondo et al, 2006;Larios, Ayala, Arredondo, Baquero, & Elder, 2009) was used to assess parents' use of appropriate boundaries for sedentary behaviors. Parents were instructed to indicate how often they engage in the particular parenting practice specified in each item on a 4-point Likert scale.…”
Section: Parental Limit Setting Of Sedentary Behaviorsmentioning
confidence: 99%
“…Some tools were found to describe only a few aspects of parenting which were not comprehensive enough to describe the patterns of parenting as a whole (Larios et al, 2009;Campis et al, 1986). Even though some tools were comprehensive, they were not suitable for the local culture, as the wording and behaviours asked were not reflecting the Eastern, especially Sri Lankan Tamil culture.…”
Section: Discussionmentioning
confidence: 99%
“…Development of the questionnaire was mainly done by devising the items from the existing tools in literature and generation of new items from the FGDs and KIIs. The same procedure was followed by researchers in Western countries in development and validation of parenting scales (Arnold et al, 1993;Campis et al, 1996;Larios et al, 2009). Sri Lankan researchers also followed the same procedures in development of tools for different purposes (Fernandopulle, 2000;Amarasinghe, 2010).…”
Section: Discussionmentioning
confidence: 99%